The Role of Reward Systems on the Productivity of Millennial and Gen Z Employees at PT Equityworld Futures Surabaya in the Industry 5.0 Era - Siti Nur Eliza Rahmawati; Ainur Rohmah; Julaika Pertiwi; Nichlah Mufidah; Muhammad Alkirom Wildan (Journal of Transformational Human Resource Management, 2025)
Industry 5.0 demands that companies develop reward systems that can increase employee motivation and productivity, especially among Millennials and Generation Z. This study uses a qualitative case study approach to examine the influence of financial and non-financial rewards at PT Equityworld Futures Surabaya. The findings indicate that bonuses and commissions are the main drivers of productivity, while non-financial rewards such as promotions, training, and overseas travel programs strengthen intrinsic motivation and loyalty. A reward system that aligns with the needs of the younger generation helps create a competitive and positive work environment, although target pressure remains a challenge that needs to be managed. Overall, the combination of financial and non-financial rewards plays a significant role in increasing employee productivity in the Industry 5.0 era.